Concurrent Binary Search Tree - Gonçalves, Hugo (2024)
This article proposes the implementation of a library in C language for a Binary Search Tree, where several concurrency control methods are offered for the most common operations performed in this data structure. An analysis of the gains or losses of each method in several replicable scenarios is presented.